De novo variants in CNOT3 cause a variable neurodevelopmental disorder - Martin, R.; Splitt, M.; Genevieve, D.; Aten, E.; Collins, A.; de Bie, C. I.; Faivre, L.; Foulds, N.; Giltay, J.; Ibitoye, R.; Joss, S.; Kennedy, J.; et al. (European journal of human genetics : EJHG, 2019)
As a result of exome-based sequencing work performed by the DDD study, de novo variants in CNOT3 have emerged as a newly recognised cause of a developmental disorder. This paper describes molecular and clinical details of 16 probands with developmental disorders and de novo CNOT3 variants. It is the first such description of the developmental phenotype associated with CNOT3 variants. Eight of these cases were discovered as part of the DDD study, while the other eight were found as a result of large-scale sequencing work performed by other groups. A highly specific phenotype was not recognised in these 16 cases. The most consistent phenotypic features seen in subjects with de novo variants in CNOT3 were hypotonia, relatively small stature, developmental delay, behavioural problems and intellectual disability. There is no easily recognisable facial phenotype, but some common dysmorphic features such as anteverted nares, thin upper lip and low set eyebrows were shared among some of the probands. Haploinsufficiency appears to be the most likely mechanism of action, with eight cases found to have protein-truncating variants. Of the other eight cases (all missense variants), three share an amino acid substitution at the same position which may therefore represent an important functional domain.